DISASTER IN THE EARLY MODERN WORLD (ABINGDON)
1 online resource
Keywords: How did early modern societies think about disasters, such as earthquakes or floods? How did they represent disaster, and how did they intervene to mitigate its destructive effects? This collection showcases the breadth of new work on the period ca. 1300-1750. Covering topics that range from new thinking about risk and securitisation to the protection of dikes from shipworm, and with a geography that extends from Europe to Spanish America, the volume places early modern disaster studies squarely at the intersection of intellectual, cultural and socio-economic history. This period witnessed fresh speculation on nature, the diffusion of disaster narratives and imagery and unprecedented attempts to control the physical world. The book will be essential to specialists and students of environmental history and disaster, as well as general readers who seek to discover how pre-industrial societies addressed some of the same foundational issues we grapple with today.